Geological investigation of river terraces along the Modi Khola valley, Parbat district, western Nepal Lesser Himalaya - Lamsal, Sudip; Sapkota, Nabaraj; Bhandari, Arjun; Gyanwali, Ishor; Paudyal, Kabi Raj; Paudel, Lalu (Journal of Nepal Geological Society, 2017)
Fluvial terraces are remnants of the former floodplain of a stream or river. Wide river valley with spectacular terraces are the well-known places of the Himalaya because of their unique morphology and history of origin. The Modi Khola and Kali Gandaki valleys in west Nepal, Lesser Himalaya are characterized by a number of spectacular river terraces. In the present study, the river terraces along the Modi Khola valley were mapped at 1:25,000 scale and their lithological and sedimentological characteristics were investigated. The river terraces along the Modi Khola are distributed in at least three levels. They are named as Godam Formation (Higger Terrace), Badagaun Formation (Middle Terrace) and the Modibeni Formation (Lower Terrace). The Godam Formation is standing out at an elevation between 860 m and 1100 m. The upper surface of the terrace is extremely rugged with karstic features. The Godam Formation is characterized by matrix-supported, calcite cemented conglomerate with angular to sub-angular clasts of calcareous shale, laminated siliceous limestone and quartzite. The Badagaun Formation (Middle Terrace) is distributed at an altitude from 700 to 860 m on both sides of the Modi Khola valley. It is deeply weathered forming a very thick (almost 3-5 m) residual soil (mostly lateritic soil). Karst features such as caves and sink holes are common in this terrace. This formation is mainly composed of matrix-supported conglomerate with granule-, cobble- and boulder-sized clasts of calcareous shale, siliceous limestone and rarely quartzite. The Lower Terrace (Modibeni Formation) is fluvial deposit consisting of rounded and subrounded clast-supported conglomerate. Both the Upper and Middle Terraces have been interpreted as cohesive debris flow facies derived from the Annapurna Range. Presence of three levels of terraces indicates at least three phase of uplift in the area in the Holocene time. The debris flow deposit in the upper and Middle Terraces indicates catastrophic outbursts from natural dams or large rock-ice avalanches in the Annapurna Range triggered probably by megaearthquakes as in Pokhara valley as suggested by Schwanghart et al. (2015).